ALGORITHM FOR DETERMINATION OF EXPONENTS PARAMETERS WHICH APPROXIMATE HEAT SINK TRANSIENT HEAT RESISTANCE - Ostrenko, V. S. (Radio Electronics, Computer Science, Control, 2011)
The algorithm is proposed for determination of exponents parameters which approximate heat sink transient heat resistance as a function of time. It permits to include the heat sink into the system for calculation of power semiconductor structure temperature.